Metody symulacyjne w badaniach preferencji z wykorzystaniem programu R - Bąk, Andrzej (Simulation Methods in the Research of Preferences Using R Computer Programme, 2008)
Simulation methods may be used in the research of consumer preferences linked with conjoint analysis. R computer programme does not offers package containing whole conjoint analysis procedure. Nevertheless various packages may be used in the research of consumer preferences and simulation analysis connection with conjoint analysis. The paper presents R packages and procedures which may be used in the research of preferences using conjoint analysis and simulation methods.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 207-214